Seamless mobility - Thorngren, Bertil; Andersson, Per; Bohlin, Erik; Boman, Magnus (Info., 2004)
The five papers in this special issue have been selected from presentations held at the 2003 Mobility Roundtable, held at Stockholm. Looks at the inevitable merge of the tele-centric and data-centric world and mobile Internet and how they have enabled mobile access in both professional and personal lifestyles. Evaluates demand, supply and culture. Opines that with future developments hard to predict new actors from other sectors, such as hotels and restaurants could, by merging their interests, provide a seamless roaming service. Conclusions drawn are that conceptions of mobility in all lifest.